Design and Implementation of a Novel Electronic Health Record Tool to Enhance the Care of Individuals with Cystic Fibrosis: The Cystic Fibrosis Note Template - Leander, David M.; Gifford, Alex H.; Mecchella, John N.; Sabadosa, Kathryn A.; Van Citters, Aricca; Snide, Jennifer A.; Nelson, Eugene C. (ACI Open, 2019)
Cystic fibrosis (CF) is a genetic disease in which dysfunction of a single protein channel leads to organ damage, resulting in chronic health problems and premature death. In the United States, medical care of individuals living with CF is delivered by care centers accredited and subsidized by the CF Foundation. CF outcomes have improved significantly through the use of collaborative networks, registry data, and research. CF clinicians are perpetually challenged to assimilate and act upon large quantities of data generated by the care of these individuals. CF Foundation accreditation also requires care centers to enter patient-level data from clinical encounters into the CF Foundation Patient Registry (CFFPR). Commercially available electronic health record systems often lack tools with sufficient context specificity and ease of use to facilitate productive interactions between clinicians and patients. We describe a CF-specific NoteWriter template built and implemented in Epic, which captures discrete data and simultaneously generates clinical documentation during ambulatory encounters. Unlike other examples of note templates in CF, this project involves SmartData Elements (SDEs) using the NoteWriter tool in Epic, which enables data to be entered in the exact way in which the CFFPR captures data. By conducting a pre-/poststudy of its use in our health system, we found that the template can expedite note completion when clinicians have adequate time to become familiar with the tool. We anticipate that the NoteWriter template will become a vehicle for delivering standardized, structured patient data to the CFFPR.
Keywords: electronic health record; coproduction; note template; cystic fibrosis